Detection of Entamoeba sp. and Helmith Eggs From Water Sources in Urban Slum Area in Bandung Municipality - Sri Yusnita Irda Sari; M. Ersyad Hamda; Adi Imam Cahyadi Cahyadi; Jasmine Maulinda Utami; Mogenes Ravichandran; Ardini Raksanagara (Faculty of Public Health, Andalas University, 2016)
Diarrhea is a waterborne disease due to consumption of contaminated food/water. People in urban slum area have highest risk to get diarrhea because of poor hygiene and sanitation as well as limited access to uncontaminated water. This study aimed to identify contamination in watersources by Entamoeba Sp and helmint eggs (Anchylostoma duodenale, Ascaris lumbricoides, Trichuris trichuria) in one of urban slum area in Bandung municipality. Samples were taken from 123 watersources (74 tap water, 21 borehole, 22 dugwell and 6 spring water) which was randomly selected in 10 RW along the Cikapundung river basin in Tamansari subdistrict during period of July-September 2015. Water samples were examined by PCR to detect Entamoeba Sp and microscopic identification for helminth eggs. 90 out of 123 samples were positive for Entamoeba Sp (59 tap water, 16 dugwell, 11 borehole and 4 spring water). Helminth egg of Ascaris lumbricoides was detected from unimproved common dugwell which had very high risk of contamination. Appropriate of water treatment prior to consumption is vastly important. Physical improvement to construct improved dugwell should be done to prevent contamination from helminth eggs in watersources.